Determinants of waste generation per capita in Catalonia (North-eastern Spain): the role of seasonal population - Saladié, Òscar (European Journal of Sustainable Development, 2016)
Seasonal population is not taken into account in waste management policies and regional differences in waste generation per capita are magnified. Here I analyze the differences among the Catalan counties (North-eastern Spain) and I compare the results if seasonal population is added or not to the resident people. Waste generation per capita in tourist areas is overestimated and actually the differences among the counties are lower than those indicated in the official data. Only reliable data will allow determining the reasons of differences in waste generation per capita and stablishing more precise objectives in waste management policies. There is a positive correlation between municipal waste generation per capita and the services sector’s contribution to GDP, a negative correlation with the percentage of population over 64 and no correlation with income per capita. Finally, taking into account territorial factors, the lowest waste generation per capita corresponds to counties with very low population densities located in inland Catalonia. Key words: Municipal waste management, seasonal population, determinants of waste generation per capita, Catalonia